Quality evaluation of some selected commercial honey products available in the market of Bangladesh - Rahman, Md Mamunur; Karmoker, Poly; Alam, Md Zinnatul (Fundamental and Applied Agriculture, 2017)
Natural honey is one of the most valued items in the market due to its unique properties and diversified usages. To ascertain the biochemical properties of commercially available honey products in Bangladesh, an experiment was conducted at Entomology and Horticultural laboratory in Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU). Honey samples of eight different commercial brands were collected and subjected to analyze analyzed on different bio-chemical parameters. Significant differences in nutritional qualities were observed. Highest TSS (total soluble solids) and total reducing sugar were observed in the product Premium honey brand of Australia, however moisture content, protein and ash percentage were found the lowest. Other foreign honey brands provided better results compare to some local originated honey products based on particular parameters especially for moisture and electrical conductivity. The results of this study suggested that although locally originated commercial honey products such as BSCIC honey, Litchi and Mustard honey from BSMRAU have meet some international quality standard level however other parameters like moisture contents and EC needs to be improved.